FAKTOR-FAKTOR YANG MEMPENGARUHI TERJADINYA HIPOTENSI INTRADIALISIS PADA PASIEN GAGAL GINJAL TERMINAL YANG MENJALANI HEMODIALISIS - Sahran, Sahran (Politeknik Kesehatan Kemenkes Bengkulu, 2018)
One of the most common complications of chronict kidney disease patientsundergoing hemodialysis is intradialytic hypotension. This study aims to identify thefactors that influence the occurrence of intradialytic hypotension in patients with end stagerenal failure undergoing hemodialysis. The study design was cross sectional recruited of81 patients of hemodialysis patients. Data were analyzed using contingency coefficient ,spearman and logistic regression. The results showed a significant relationship betweenhistory of heart disease, intradialytic weight gain and albumin levels and the incidence ofintradialytic hypotension (p <0.05). The most influence variables that influence onincidence of intradialytic hypotension was history of heart disease with OR=3.525. Nurseshave to increase their capability in monitoring factors that influence intradialytichypotension especially in pre, intra, and post hemodilaytic, giving education about waterand dietary consumption. to increase their capability in the provision of nursing care forhemodialysis patients.